Kajian Awal Kepadatan Meiofauna dalam Paya Bakau Teluk Mengkabung, Sabah - Mohd Long, Shabdin; Karim, Rusdan (1990)
A study on meiofaunal densites was carried out in Teluk Mengkabung, Sabah from August 1988 to January, 1989. The meioJauna was sampled and several physico-chemical characteristics on the interstitial water was measured. The density of meiofauna in Teluk Mengkabung, Sabah was between 292-1193 individuals 1()l cm-2. Nematodes was the dominant taxon followed by harpacticoid copepods. The density of nematodes was between 238-996 individuals 1()f cm-2 and harpacticoid copefJod was 26-216 individuals 1()J cm-2. The meiofaunal densities of Teluk Mengkabung, Sabah were found to be influenced by salinity, dissolved oxygen and porosity of the interstitial water.